PENGARUH KUALITAS AUDIT DAN TENURE AUDIT TERHADAP AUDIT REPOT LAG (ARL) DENGAN SPESIALISASI AUDITOR INDUSTRI SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan–Perusahaan Manufaktur yang Listing di BEI tahun 2010–2012) - Permata Dewi, Sandiba Giwang; Afri Yuyetta, Etna Nur (Diponegoro Journal of Accounting, 2014)
This research aims to analyze how audit quality and tenure audit correlate affect audit report lag with auditor industry specialization as a moderating variable of empirical studies on manufacturing companies listed in Bursa Efek Indonesia during the period of 2010 – 2012. Audit quality using earning surprise benchmark proxy and tenure audit are utilized as independent variables. Dependent variable in this research is audit report lag. Data used in this research are collected from financial statements of manufacturing companies listed in IDX fact book and Indonesian Capital Market Directory. The population of this research comprise of manufacturing companies listed in Bursa Efek Indonesia during the period of 2010 – 2012 with a total of 75 companies. The samples are determined using purposive sampling method. Data used in this research are secondary data from financial statement of the aforementioned manufacturing companies. Analysis of data is carried out using multiple regression method with the aid of SPSS Version 16 computer program. This research reveals that tenure audit moderated by auditor industry specialization shows shorter audit report lag compared to that of the non-specialists, whereas the audit quality with earning surprise benchmark proxy is not moderated by auditor industry specialization. Good audit quality moderated by auditor industry specialization does not contribute to audit report lag.